How To Use AfricArXiv To Increase Discoverability Of Your Research Output - Obanda, Johanssen; Havemann, Jo (My University, 2021)
A presentation about AfricArXiv hosted by Eider Africa, presented on September 10, 2021.
Keywords: research discoverability; AfricArXiv; journal publishing